Corticosteroid use in neonatal hypotension: A survey of Canadian neonatologists - Ashraf Kharrat; Yenge Diambomba; Amish Jain (Elsevier, 2024)
Objective: To assess prescribing practices and perspectives regarding the use of corticosteroids in the management of neonatal hypotension. Methods: Cross-sectional questionnaire-based electronic survey of neonatologists (n = 206) practicing at tertiary neonatal intensive care units across 30 academic centres in Canada. Results: The overall response rate was 33% (72/206), with a completion rate was 94%. Most (48/72, 64%) worked in a unit that covered both inborn and outborn infants, and 53% (37/70) worked in units with >100 very low birth weight infants admitted annually. Among the 72 respondents, 39% use a loading dose, of whom most (57%) use 2 mg/kg. Dosing ranges were variable, most using either 0.5 mg/kg or 1 mg/kg, q6h. Among the 56% (40/72) of neonatologists who reported measuring cortisol before initiation of hydrocortisone, cut-offs for initiation of hydrocortisone varied from <100 to <500 nmol/L, most of whom (48%) used <100 nmol/L. Of 71 respondents, 92% (65) indicated that a randomized control trial examining the use of corticosteroids in neonatal hypotension is needed, of whom 52% (37) indicated that the intervention group should receiving hydrocortisone after one vasopressor/inotrope. Conclusions: This survey provides insight into the prescribing practices of tertiary neonatologists with regards to the use of corticosteroids in neonatal hypotension. While corticosteroids are frequently prescribed, there is variability in the indication, dosing, and duration of corticosteroid use. The findings from this survey can be used to inform further research, including a clinical trial, regarding the practice in the management of neonatal hypotension.